A Feasibility study on burn/wound dressings - Berenguer, Kristine Abigail L.; Dy, Roland Daniel Brian R.; Jacobe, Ruth S. (Diliman, Quezon City College of Engineering, 2000)
Carraderm Hydrogel is a dressing especially made for treating highly-infected wounds and burns. It is the locally-produced dressing of its kind. Its main competitive edge in the pharmaceutical market is that it is economically-priced compared to its imported counterparts, mainly because it makes use of a local seaweed extract, carrageenan, which is highly abundant in the country. A market study was done to determine the viability of the product's entry into the existing market. The product shall be made available in the National Capital Region, particularly in secondary and tertiary government and private hospitals. From the market analysis, it was found that the product will be able to capture 16.09% of the market on its introductory year, with the said market share increasing every year, reaching 17.29% share of the market by the end of the year 2005. The total selling and distribution expenses, consisting of advertising and promotions, salaries of the company's marketing department, and other marketing-related expenses, amount to P53,075,932.12. at the end of the market study, it was concluded that introducing the product into the market is viable, on the basis that the product's distinctive edge over its competitors will make it succeed in the market. From the technical analysis of the production of the product, it was determined that the plant has an overall capacity of 374,400 Carraderm Hydrogel sheets for the first year of operations. The value is constant until the fourth year of operations. In terms of utilization, 86% of the total plant capacity will be utilized for year 2001. The corresponding utilization rates of the production line for the succeeding four years are as follows: 90% (year 2002), 94% (year 2003), 98% (year 2004) and 102% (year 2005). The over-utilization during the fifth year is due to the overtime hours rendered by the packers. It must be noted that the machines are never over utilized. The total manpower requirements will be 10 production workers/direct laborers, 10 medical representatives, and 15 administrative personnel. There will be 260 working days per year, 22 working days per month, and 5 working days per week. There will be one eight-hour shift in the production area per day. From the analysis of the different technical considerations of the study, it was concluded that the project is technically feasible since the size, location, and production processes of the project are commensurate and appropriate to the demand, the engineering aspects of the project are reasonably well-defined and found to be workable, adequate and acceptable, the input resources that the project requires are available in the required quantities and qualities of the dressing on a continuing and dependable basis. The company that will produce the product is structured as a corporation, mainly because of the need for pooling of initial capital from the owners. With an estimated project start-up cost of P18,000,000.00 it is therefore imperative that there be adequate funding for the project. Different departments comprise the company, with each department differentiated according to its function. An organizational structure is developed in the study. The total manpower requirements for the various sections of the enterprise are also given in the study. A total of 35 employees will be needed in the implementation of the project. The project was also found to be financially feasible. It showed a positive net present value of P35,763,296.52. Likewise, its internal rate of return was 63.21%, almost twice the minimum attractive rate of return set at 30%. Funding from financial institutions can also be obtained, and the project was also found to be capable of paying incurred debts, aside from having a satisfactory output. The venture would be able to recover its investment in a span of 5.78 months, based on computations covering the first five years of operations. The project will generate an income ranging from P15,066,299.3 in the first year to P24,594,221.05 in the fifth year. Finally, the project is not only a profit-generating venture. From the social profitability study, it was concluded that the project is likewise beneficial to society. Several sectors of society which gain, whether directly or indirectly, from national government, and even the environment. Therefore, venturing into the production of Carraderm Hydrogel is a feasible undertaking.
Feasibility Study
Submitted in partial fulfillment of the course requirements in IE 153 : Project Development and Management
Keywords: Wounds and injuries--Treatment.; Burns and scalds; Carrageenan; Participatory monitoring and evaluation (Project management)